Интервенционная нейрорадиология в Запорожье: история, современное состояние, перспективы развития - Матерухин, А. Н.; Полковников, А. Ю.; Макаренков, А. Л.; Матерухін, Аркадій Миколайович; Полковніков, Олексій Юрійович (My University, 2013)
Описана история становления сосудистой нейрохирургии в мире и Украине. Освещена история становления нейрохирургической службы в Запорожской области с середины прошлого века и до настоящих дней. Рассмотрена история оказания медицинской помощи пациентам с цереброваскулярной патологией в Запорожской области, в частности на базе Запорожской областной клинической больницы. Описаны современные достижения запорожской эндоваскулярной хирургии и рассмотрены перспективы развития службы. Рассмотрена структура оказания помощи пациентам с цереброваскулярной патологией в регионе. Описано історію становлення судинної нейрохірургії в світі та Україні. Висвітлено історію становлення нейрохірургічної служби в Запорізькій області з середини минулого століття і донині. Розглянуто історію надання медичної допомоги пацієнтам з цереброваскулярною патологією в Запорізькій області, зокрема на базі Запорізької обласної клінічної лікарні. Описано сучасні досягнення запорізької ендоваскулярної хірургії та розглянуто перспективи розвитку служби. Розглянуто структуру надання допомоги пацієнтам з цереброваскулярною патологією в регіоні. The article describes the history of the formation of vascular neurosurgery in the world and Ukraine. The history of formation of the neurosurgical service in the Zaporozhye region since midcentury to the present day is covered in the article. The history of medical care to patients with cerebrovascular disease in the Zaporozhye region, in particular on the basis of Zaporizhzhya Regional Hospital is analyzed. Recent advances of Zaporozhye endovascular surgery and the prospects of development of the service are described. The structure of the care of patients with cerebrovascular disease in the region is determined.
Інтервенційна нейрорадіологія в Запоріжжі: історія, сучасний стан, перспективи розвитку
Interventional Neuroradiology in Zaporizhya: history, current state and prospects for development
Keywords: эндоваскулярная нейрорентгенохирургия; Запорожская областная клиническая больница; перспективы развития; цереброваскулярная патология; нейрохирургическая служба; ендоваскулярна нейрорентгенохірургія; Запорізька обласна клінічна лікарня; перспективи розвитку; цереброваскулярна патологія; нейрохірургічна служба; endovascular neuroradiology; Zaporizhya Regional Hospital; the prospects for development; cerebrovascular disease; neurosurgical service